Origin of the structure-directing effect resulting in identical topological open-framework materials - Xin, Liang (Sci Rep, 2015)
In the synthesis of zeolites and related crystalline materials with open-frameworks, a single structure is obtained in the presence of many different templates, known as the “one-structure/multiple-templates” phenomenon. However, the reasons behind this phenomenon have yet to be elucidated. By analyzing the possible starting point of crystallization in several “one-structure/multiple-templates” systems and applying the molecular dynamics simulation to such systems, we found that the template-framework binding free energy level or charge transfer (exchange) degree was the key to the structure-directing effect of a template. This discovery explains why the structure-directing effect of a template can be affected by many variables, such as the nature of the source materials, molar composition of the initial reaction mixture (recipe), mineralizers, type of solvent, and heating temperature. In the synthesis of zeolites and related crystalline materials with open-frameworks, the template or organic additive played a topological structure-directing role instead of a structure-directing role.